THE SENSES OF PRECARIOUSNESS IN THE WORK PRECARIOUS LIFE OF JUDITH BUTLER - Araújo Sial Neto, Albérico (2022)
The present article aims analyze, in the work Precarious Life, the two senses attributed to precariousness. This work, from the assignment of the political and ethical aspect to the aforementioned concept, proves to be fundamental for Judith Butler’s future reflections. Furthermore, precariousness is related to the notions of recognition. This is because the lives that are outside of recognition schema are the same lives whose deaths are not regretted, they are not regrettable, that is, precarious life. Thus, an ethic that seems the precariousness of the other as essential is taken into account, an ethics that can be called the ethics of recognition. Such ethics arises from the understanding that responses to the violations suffered must have as a starting point the adoption of the condition of vulnerability and aggression as pillars of political life.